Village-Based Community Health Promotion in Rural Public Health Posts: Clinical and Behavioral Changes and Factors - Mi Sook Jung; Sun Suk Bhin; Hyun Mi Park (Korean Association of Health and Medical Sociology, 2026)
This study aimed to examine changes in clinical indicators, health behaviors, and health status following participation in a village-based health promotion program, to assess variation in these changes across public health posts (PHPs), and to identify individual-level factors contributing to variability in change trajectories. A multi-site pre-post observational study was conducted using data from 247 participants across seven PHPs in Sejong city. Multidomain outcomes were assessed at baseline and post-intervention. Mixed-effects models were applied to examine within-individual change, between-site differences, and variability in change patterns, while adjusting for age, sex, comorbidity burden, and depression. Significant time effects were observed for waist circumference (p < .001), systolic blood pressure (p < .001), diastolic blood pressure, physical activity stage, and oral discomfort. Significant between-site differences were identified across multiple outcomes, and time-by-site interactions were found for systolic blood pressure, glucose status, dietary assessment score, physical activity stage, and toothbrushing behavior, indicating heterogeneity in program effects across PHPs. In addition,individual-level factors contributed to change patterns, with age and comorbidity burden associated with clinical outcomes, and depression associated with behavioral and perceived health outcomes. Community-based health promotion programs in rural settings produce outcome-specific and context- dependent effects rather than uniform improvements. The observed variation across public health posts reflects context-specific implementation processes, underscoring the need for flexible, context-sensitive approaches that enable adaptation to local conditions while sustaining program effectiveness.